Enzymatic transesterification of palm stearin and olein blends to produce zero-trans margarine fat - Sellami, Mohamed (BioMed Central, 2012)
BACKGROUND: Food industries aim to replace trans fat in their products by formulations having equivalent functionality and economic viability. Enzymatic transesterification can be a technological option to produce trans free fats targeting commercial applications. RESULTS: Palm stearin and palm olein blends in different ratios were enzymatically transesterified in a solvent free system using a Rhizopus oryzae lipase immobilised onto CaCO(3) to produce a suitable fat for margarine formulation. Slip melting points and triacylglycerols profiles were evaluated upon transesterification. Results indicated that all transesterified blends had lower slip melting points than their non transesterified counterparts. Furthermore, the triacylglycerols profile showed a decrease in the concentration of the high melting point triacylglycerols. The rheological analysis showed that margarine prepared with the transesterified blend showed a better spreadability than that of a control margarine prepared with non transesterified fat. Adding powder of dry bark orange to margarine preparation improved its colour and fairly affected its spreadability and rheological behaviour. The margarine prepared with transesterified fat displayed a rheological behaviour that was comparable to that of commercial sample. CONCLUSIONS: This study is an ecofriendly approach to the utilization of relatively low value bioresources like palm stearin and palm olein for making margarine free of trans fatty acids that are now implicated as risk factor for heart diseases.